Hypoalbuminemia as a Predictor of Outcomes in Acute Myeloid Leukemia: A Systematic Review and Meta-Analysis - Jacobs, Christin Yosefin; Nugroho, Fajar Prianto; Amelia, Sesa; Pannaausten, Davin; Almaszahra, Annisa Naufal; Prayogo, Andi Bagus; Jessica; Pranata, Jimmy Angga (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background : In acute myeloid leukemia (AML), hypoalbuminemia has been observed at diagnosis and during treatment, often correlating with poor clinical outcomes such as reduced remission rates, increased treatment-related toxicity, and shorter overall survival (OS). This systematic review and meta-analysis aim to investigate the prognostic value of hypoalbuminemia in patients with AML. Methods : A comprehensive literature search was conducted across PubMed, EMBASE, and Scopus to identify relevant studies published up to January 5, 2025. The search strategy included a combination of Medical Subject Headings (MeSH) terms and keywords such as “hypoalbuminemia,” “acute myeloid leukemia,” “AML,” “serum albumin,” “prognosis,” and “outcomes.” Boolean operators (AND, OR) were applied to refine the search. Result : This systematic review and meta-analysis included 10 studies with a total sample size of 4,105 participants, of which 2,134 were male, comparing normal albumin levels to hypoalbuminemia across diverse populations. The meta-analysis comparing OS between AML patients with hypoalbuminemia and normal serum albumin levels shows a pooled HR of 1.08 (95% CI: 0.81–1.44). Conclusions : While this meta-analysis suggests a potential association between hypoalbuminemia and poorer OS and DFS in AML patients, the lack of statistical significance and high heterogeneity caution against definitive conclusions.